Transition to Medical College: Dynamics of Depression, Internet Addiction and Nutritional Status among Junior Medical Students - Tarun Prakash Maurya; Limalemla Jamir; Rajeev Aravindakshan (Medsci Publications, 2022)
Background: The initial years of a medical student's life can be challenging. Coping mechanisms with internet technology can have adverse health effects. This study assessed the depression, internet addiction and nutritional status among junior medical students. Materials and methods: This cross-sectional study was conducted among first and third semester medical students of a new central institute in South India. Depression and internet addiction were assessed by Patient Health Questionnaire-9 and Young's Internet Addiction Test, respectively. Mann Whitney U test, Pearson's Chi-squared/Fishers Exact tests and Structural Equation Modelling (SEM) were applied. Results: A total of 97 medical students were studied. This comprised 60 male and 37 female students. Mean(SD) age was 19.3 (1.87) years. Most (68%) students were from rural backgrounds. Depression was higher among first semester students (p=0.017), whereas internet addiction was higher among third semester students (p=0.002). Prevalence of underweight, overweight and obesity were 7.2%, 18.6% and 35%, respectively. Correlates of internet addiction were previous hostel stay (p=0.047), nutritional status (p=0.043) and social media use (p<0.000). SEM explained the relationship of semester, depression and duration of smart phone usage with internet addiction. Conclusion: Depression and internet addiction was higher among first semester and third semester students, respectively. Nutritional problems were prevalent across semesters.